Towards sustainable health care systems: Strategies in health insurance schemes in France, Germany, Japan and the Netherlands ; a comparative study - Klaus-Dirk Henke; Jonas Schreyögg (Technische Universität Berlin, Fakultät Wirtschaft und Management, 2004)
In all four countries health care expenditures grow while the revenue remains at the same level or even shrinks in many cases. Due to medical progress, ageing and many other factors the gap is widening over time. The pay-as-you-go approach is running against limits either with rising employer and employee contribution rates as is the case in the so-called Bismarck-Systems or with higher taxes in the so-called Beveridge-systems. There are differences regarding the solutions of each country to tackle the described challenge and they might be able to learn from each other if they are compared. Therefore the study compares the health care systems of France, Germany, Japan and the Netherlands. Due to the complexity of the different institutional settings it seems necessary to select certain criteria in order to make a comparison at all possible. The comparison is divided into three different sections. The institutional and organizational framework as first section compares the general organization of social health insurance in all four countries. It comprises the benefit structure, the enrolment, ownership issues and other criteria. The second section focuses on the funding of social health insurance comparing the different approaches according to criteria like contribution rates, contribution assessment bases, burden of contributions and others. The final section analyses different strategies in the provision and purchasing of health services in the four countries. Next to other hospital ownership infrastructure characteristics play an important role in this section. In the last part of the study certain lessons are drawn from the comparison of the four countries. Furthermore certain developments are described which can be anticipated for the future of social health insurance systems. – – Sowohl die demographische Entwicklung als auch vielfältige medizinische und medizinisch-technische Fortschritte führten in den letzten Jahren zu starken Ausgabensteigerungen in den sozialen Krankenversicherungssystemen. Neben Deutschland sind von dieser Entwicklung auch andere Länder mit sozialen Krankenversicherungssystemen betroffen. Die vorliegende Studie nimmt einen systematischen Vergleich zwischen verschiedenen Ländern vor, deren Gesundheitssystem auf einer sozialen Krankenversicherung aufbaut: Deutschland, Frankreich, Japan und die Niederlande. Anhand definierter Kriterien werden die unterschiedlichen Ausprägungsformen im Hinblick auf den organisatorischen und institutionellen Rahmen, die Mittelaufbringung sowie die Leistungserbringung bzw. die Mittelverwendung der einzelnen Länder verglichen. Anschließend werden mögliche Handlungsstrategien aus dem Vergleich abgeleitet, um den zukünftigen Herausforderungen zu begegnen und eine nachhaltige Entwicklung der sozialen Krankenversicherungssysteme sicherzustellen. Abschließend werden bestimmte Entwicklungen beschrieben, die für die sozialen Krankenversicherungssysteme antizipiert werden können.
Keywords: 360; Gesetzliche Krankenversicherung; Gesundheitskosten; Gesundheitsfinanzierung; Vergleich; Deutschland; Frankreich; Japan; Niederlande